Suture granuloma with false‐positive finding on PET/CT after gastrectomy for gastric cancer. Issue 4 (November 2015) - Tsujita, Eiji; Ikeda, Yasuharu; Kinjo, Nao; Yamashita, Yo‐ichi; Kumagai, Reiko; Taguchi, Ken‐ichi; Yamaguchi, Shohei; Minami, Kazuhito; Yamamoto, Manabu; Morita, Masaru; Toh, Yasushi; Okamura, Takeshi
Abstract: This study is a case report on a 49‐year‐old woman who had a gastrectomy and lymphadenectomy for pStage IIIa gastric cancer. Shortly after a 12‐month course of adjuvant chemotherapy, CT showed a nodule adjacent to the gallbladder. High 18 F‐fluorodeoxyglucose accumulation was detected, with a standardized uptake value of 10. Therefore, laparoscopic excision was performed for diagnosis and treatment. The histopathological finding was suture granuloma. Suture granulomas with high standardized uptake values on PET scans are uncommon and often cause surgeons to provide an inaccurate diagnosis. Our study suggests that suture granuloma should be included in the differential diagnosis of a new or recurrent mass detected in patients with a history of prior surgery; however, surgeons must bear in mind that false‐positive fluorodeoxyglucose‐PET results can be observed in suture granuloma.